Determinants of Academic Performance in Public Secondary Schools in Kapenguria Division-Kenya: Assessing the Effect of Participation in Selected CoCurricular Activities - Kapelinyang , Rionosia Philemon; Lumumba , Kutotto Patrick (African Journal of Education,Science and Technology (AJEST), 2017)
The relationship between learners’ participation in co-curricular activities and their performance in academics remains confusing. Although, some studies report positive impacts of co-curricular activities, a significant number reports negative impacts. The present study therefore examined determinants of academic performance in public secondary schools by drawing upon the effect of selected co-curricular activities. The study adopted the concurrent mixed methods design for purposes of examining both quantitative and qualitative data. Both stratified and simple random sampling techniques were used to a draw a sample comprising of 250 students, 15 co-curricular teachers, and 5 Principals. Descriptive statistics were used to explore quantitative data while thematic analysis was used to examine qualitative data. Multiple regressions model was used to establish determinants of academic performance from the selected co-curricular activities. The study concluded that athletics, music, and soccer were positive and significant determinants of students’ academic performance. There is therefore need for provision of facilities that could promote these activities.